1983
DOI: 10.2307/2259589
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Succession Following Slash and Burn Agriculture in North-Eastern India: I. Biomass, Litterfall and Productivity

Abstract: Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at http://www.jstor.org/page/info/about/policies/terms.jsp. JSTOR's Terms and Conditions of Use provides, in part, that unless you have obtained prior permission, you may not download an entire issue of a journal or multiple copies of articles, and you may use content in the JSTOR archive only for your personal, non-commercial use.Please contact the publisher regarding any further use of this work. Publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…Similar cases have been found in other studies of swidden fields, abandoned plantations and pasture (Tabarelli & Mantovani, 1999;Mitche et al, 2000;Oliveira, 2002). Furthermore, Toky & Ramakrishnan (1983) reported that in swidden fallow succession in northeastern India, species diversity increased with fallow age during the first 15-20 years. Relationships between relative abundance of species and stand age differed among species, indicating that species achieved their highest abundance at different times during succession as proposed in the model of succession by Gómez-Pompa & Vázquez-Yanes (1981) and Finegan (1984).…”
Section: Discussionsupporting
confidence: 88%
“…Similar cases have been found in other studies of swidden fields, abandoned plantations and pasture (Tabarelli & Mantovani, 1999;Mitche et al, 2000;Oliveira, 2002). Furthermore, Toky & Ramakrishnan (1983) reported that in swidden fallow succession in northeastern India, species diversity increased with fallow age during the first 15-20 years. Relationships between relative abundance of species and stand age differed among species, indicating that species achieved their highest abundance at different times during succession as proposed in the model of succession by Gómez-Pompa & Vázquez-Yanes (1981) and Finegan (1984).…”
Section: Discussionsupporting
confidence: 88%
“…Increased species diversity, reduced species dominance and increased above-ground net primary productivity in a 20-yr-old fallow in comparison with 1-, 10-and 15-yr-old stands [23] Plants TE…”
Section: Appendixmentioning
confidence: 98%
“…In general, succession of pioneer vegetation following suspension of cultivation occurred rapidly in the early stages of regeneration, followed by delayed recovery of woody biomass [10,21,23].…”
Section: Vegetation Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were conducted on biomass accumulation in secondary succession of fallow of traditional shifting cultivation area (Nakano, 1978(Nakano, , 1992Ewel et al, 1981;Uhl et al, 1981Uhl et al, , 1982aToky & Ramakrishnan, 1983;Nemoto & Pongskul, 1985;Uhl, 1987;Saulei et al, 1992). Ohtsuka (1999) studied the causes of species replacement of early herbaceous stages of sewndary succession in Northeast Borneo.…”
mentioning
confidence: 99%